Cognitive dysfunction after cardiac surgery - Yoshitani, Kenji; Ohnishi, Yoshihiko (Masui. The Japanese journal of anesthesiology, 2009)
The advancement of surgical and anesthetic techniques reduced cardiac morbidity and mortality. As a result, the attention has been focused on the perioperative cerebral complication, which contribute to more than 20% of perioperative deaths. Cognitive dysfunction is associated with increased medical costs, decreaged quality of life, and mortality. However, the incidence of cognitive dysfunction has a wide variety due to methodological variations in evaluating cognitive dysfunction, showing the complexity of cognitive dysfunction. The score of cognitive test can include learning effect and natural decline of cognitive dysfunction in elderly population. The research including the control group seems to overcome these issues, but still remains to have problems. Further, patients with cardiac disease have comorbid factors to induce postoperative sequelae compared to healthy population. We describe these issues which require continued researches.